2006
DOI: 10.1051/0004-6361:20053029
|View full text |Cite
|
Sign up to set email alerts
|

$\mathsf{\alpha}$ Eridani: rotational distortion, stellar and circumstellar activity

Abstract: We explore the geometrical distortion and the stellar and circumstellar activity of α Eri (HD 10144), the brightest Be star in the sky. We present a thorough discussion of the fundamental parameters of the object for an independent determination of its rotational distortion. We used stellar atmosphere models and evolutionary tracks calculated for fast rotating early-type stars. If the star is a rigid rotator, its angular velocity rate is Ω/Ω c 0.8, so that its rotational distortion is smaller than the one infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
101
3
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(119 citation statements)
references
References 67 publications
13
101
3
2
Order By: Relevance
“…The present calibration can then provide a first step for the interpretation of spectra emitted by rotating early-type objects, as already shown in Levenhagen et al (2003); Neiner et al (2003); Zorec et al (2005);Vinicius et al (2006);Frémat et al (2006); Martayan et al (2006Martayan et al ( , 2007; Floquet et al (2000Floquet et al ( , 2002.…”
Section: Effects Related To the Rotationsupporting
confidence: 60%
See 1 more Smart Citation
“…The present calibration can then provide a first step for the interpretation of spectra emitted by rotating early-type objects, as already shown in Levenhagen et al (2003); Neiner et al (2003); Zorec et al (2005);Vinicius et al (2006);Frémat et al (2006); Martayan et al (2006Martayan et al ( , 2007; Floquet et al (2000Floquet et al ( , 2002.…”
Section: Effects Related To the Rotationsupporting
confidence: 60%
“…objects whose atmospheres can be modeled in the framework of hydrostatic and radiative equilibrium approximations. However, since both the photospheric and the circumstellar components of the BD are spectroscopically well separated, it can also be used to study some "peculiar" objects, like: i) Be stars (Divan & Zorec 1982;Zorec 1986;Zorec & Briot 1991;Chauville et al 2001;Zorec et al 2005;Vinicius et al 2006); ii) objects with the B[e] phenomenon (Cidale et al 2001); iii) chemically peculiar stars (He-W group) (Cidale et al 2007). …”
Section: The Bcd Systemmentioning
confidence: 99%
“…This strong flattening could not be explained by the commonly adopted stellar rotation models, and two possibilities were proposed to account for it: differential rotation (Jackson et al 2004), and a residual circumstellar disk (Carciofi et al 2008). By studying the time variation of Hα line profiles, Vinicius et al (2006) showed that a weak but measurable emission (relative to a reference spectra) was detectable at the epoch of the VLTI/VINCI observations; this supports the hypothesis of a residual disk.…”
Section: Introductionmentioning
confidence: 82%
“…Previous spectrally resolved interferometric observations (Meilland et al 2007a,b) and spectroscopic follow-ups (Miroshnichenko et al 2003;Vinicius et al 2006) showed evidence that the kinematics in the equatorial plan was dominated by rotation. Thus, because of the lack of available measurements for our targets and the introduction of additional parameters needed to take into account the incoherent scattering effect, we decided to neglect the expansion in the equatorial disk (i.e., V 0 = V ∞ = 0 km s −1 ).…”
Section: Emission Line Broadening By Incoherent Scatteringmentioning
confidence: 93%